ALIH KODE DAN CAMPUR KODE DALAM INTERAKSI PEMBELAJARAN BAHASA INDONESIA DI SMA NEGERI 7 SURAKARTA - Maszein, Hana; Suwandi, Sarwiji; Sumarwati, Sumarwati (Universitas Sebelas Maret, 2019)
This type of research includes qualitative descriptive research. The selected samples are class XII IPS 5, XII IPS 1 and XII IPS 4 with purposive sampling sampling technique. Source of data used in the form of document document analysis. Technique of data collecting used with technique of free libat captive, recording technique and technique of note. Data analysis technique used in this research is interactive analysis model. The result of this research is finding the form of internal code transfer: (1) switch code from Indonesian to Javanese (2) switch code from Java to Indonesian language. The form of external codes is found: (1) switch code from Indonesian to foreign (English) (2) switch code from Indonesian to foreign (Arabic). From the research results found: 1) mix the word tangible code, 2) mix the tangible code phrase, 3) mix the tangible code clause, 4) mixed tangible code of the word. Factors that influence the use of code transfers include: 1) speakers, 2) speaking partners, 3) presence of third persons, 4) subject, 5) to arouse sense of humor, 6) to be prestigious. Critical factors include: 1) speaker and personal speaker, 2) talk partner, 3) residence and time of conversation, 4) speech mode, 5) topic, 6) function and purpose, 7) variety and level speak the language. The functions of code transfer and code interfacing include: 1) clarifying and clarifying statements, 2) quoting other people's conversations, 3) avoiding rough and smooth forms.